Effects of infrequent dried distillers grain supplementation on spring-calving cow performance - Bennett, B.W.; Waggoner, Justin W.; Jaeger, John R.; Sexten, Andrea K.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Feed and supplement costs and the expenses associated with delivery of winter supplements account for a large proportion of the total operating expenditures for cow-calf producers. Cattle grazing low-quality dormant native range (<6% crude protein) typically are unable to consume sufficient protein from the forage base, which limits microbial activity and forage digestion. Supplemental protein often is required to maintain cow body weight and body condition score during the last trimester of pregnancy. Low cow body condition scores at calving are common and may negatively affect lactation, rebreeding rates, and calf weaning weight. Failure to maintain proper nutritional status during this period severely affects short-term cow performance, reduces overall herd productivity, and limits profit potential. The most effective means of supplying supplemental protein to cows consuming dormant native range is to provide a small amount of high-protein feedstuff (>30% crude protein). Dried distillers grains with solubles (DDGS) are a by-product of the ethanol refining process. Distillers grains supply the recommended 30% crude protein level, are readily available, and often are favorably priced compared with more traditional feedstuffs. With the rising costs of inputs in today’s cow-calf sector, reducing cost is necessary to maintain viability of the national cowherd. Reducing the frequency of supplementation results in less labor and fuel use, effectively reducing input costs; however, this is viable only as long as cow performance is maintained at acceptable levels. Therefore, the objective of this study was to examine the effects of infrequent supplementation of dried distillers grains with solubles on cow body weight and body condition score.
Keywords: Cattle; Dried distillers grains with solubles (DDGS); Cow performance; Nutrient composition